The Drosophila Neprilysin 4 gene is essential for sperm function following sperm transfer to females. - Ohsako, T.; Shirakami, M.; Oiwa, K.; Ibaraki, K.; Karr, T.L.; Tomaru, M.; Sanuki, R.; Takano-Shimizu-Kouno, T. (Genes & Genetic Systems, 2021)
Sperm are modified substantially in passing through both the male and the female reproductive tracts, only thereafter becoming functionally competent to fertilize eggs. Drosophila sperm become motile in the seminal vesicle; after ejaculation, they interact with seminal fluid proteins and undergo biochemical changes on their surface while they are stored in the female sperm storage organs. However, the molecular mechanisms underlying these maturation processes remain largely unknown. Here, we focused on Drosophila Neprilysin genes, which are the fly orthologs of the mouse Membrane metallo-endopeptidase-like 1 (Mmel1) gene. While Mmel1 knockout male mice have reduced fertility without abnormality in either testis morphology or sperm motility, there are inconsistent results regarding the association of any Neprilysin gene with male fertility in Drosophila. We examined the association of the Nep1-5 genes with male fertility by RNAi and found that Nep4 gene function is specifically required in germline cells. To investigate this in more detail, we induced mutations in the Nep4 gene by the CRISPR/Cas9 system and isolated two mutants, both of which were viable and female fertile, but male sterile. The mutant males had normal-looking testes and sperm; during copulation, sperm were transferred to females and stored in the seminal receptacle and paired spermathecae. However, following sperm transfer and storage, three defects were observed for Nep4 mutant sperm. First, sperm were quickly discarded by the females; second, the proportion of eggs fertilized was significantly lower for mutant sperm than for control sperm; and third, most eggs laid did not initiate development after sperm entry. Taking these observations together, we conclude that the Nep4 gene is essential for sperm function following sperm transfer to females.